Management of colorectal anastomotic leakage using endoscopic negative pressure therapy with or without protective ostomy: a retrospective study - Şandra-Petrescu, Flavius Ionuţ; Tzatzarakis, Emmanouil; Kähler, Georg; Reißfelder, Christoph; Herrle, Florian (International journal of colorectal disease, 2021)
Purpose  Management of colorectal anastomotic leakage (AL) is patient-oriented and requires an interdisciplinary approach. We analyzed the management of AL according to its severity and presence of ostomy and proposed a therapy algorithm. - Methods  We identified all patients who underwent colorectal surgery and developed an AL in our clinic between 2012 and 2017. The management of AL was retrospectively analyzed according to the severity grade: asymptomatic (A), requesting interventional or antibiotic therapy (B), undergoing re-operation (C). The groups were compared according to the leakage characteristics, presence of ostomy, and patient clinical conditions. - Results  We identified 784 consecutive patients meeting the inclusion criteria. Of these, 10.8% experienced an AL (A = 18%, B = 48%, and C = 34%). The rate of successful ostomy closure was 100% (A), 68% (B), and 62% (C), respectively. Within group B, 91% of the patients were treated solely by endoscopic negative pressure therapy (ENPT), whereas 37% of the patients within group C required ENPT in addition to surgery. Seven cases within group B (17%) required no protective ostomy (nOB) during ENPT which was itself shorter and required less cycles in comparison to group B with ostomy (OB) (p = 0.017 and 0.111, respectively). Moreover, the leakage distance to anal verge was higher in the OB subgroup (p < 0.001). - Conclusion  ENPT for the treatment of colorectal AL is efficient in combination with operative revision or protective ostomy. In selected patients, it is feasible also in the absence of a protective ostomy.
Gesehen am 21.08.2023